Poučevanje strategij za učenje besedišča pri pouku nemščine v slovenskih gimnazijah - Retelj, Andreja (Vestnik za tuje jezike, 2015)
The aim of the study was to find out the type and the frequency of vocabulary learning strategies that German language teachers teach in their classes. An online questionnaire which included 37 vocabulary learning strategies based on Schmitt's (1997) and Nation's (2001) taxonomies was administered to 72 German teachers. The results revealed that all vocabulary learning strategies were instructed in German as foreign language lessons in Slovenia; however, 10 strategies were instructed often, 19 strategies occasionally and 8 strategies rarely. None of the strategies were instructed very often. The strategies that teachers often taught in their classes included learning the meaning from context, guessing and active use of words. The strategies that were occasionally instructed cover also other aspects of word knowledge. Strategies that promote memorization of words were rarely instructed. We can conclude that German teachers with the deliberate instruction of vocabulary learning strategies contribute to learners' autonomy in learning German language and indirectly in further learning of foreign languages.
Keywords: German; nemščina; učenje in poučevanje tujih jezikov; didactic method; didaktika; besedišče; leksikalne zmožnosti; srednješolsko izobraževanje; Slovenia; Slovenija